Technological effectiveness of urban transport in selected Polish cities - Slawomira Hajduk (Institute of Economic Research (IER), 2017)
Research background: An efficient and effectively functioning transport in the city is of great importance both for the people residing in its territory, as well as companies doing business there. However, apart from a positive impact, transport also carries many social costs including congestion, traffic accidentsand a negative influence on the natural environment. Consequently, urban transport is an increasingly important area of city management. Purpose of the article:The aim of this study is to analyze and to assess the transport technological effectivenessin selected Polish cities.The author received a ranking of cities and identified ways to improve the efficiency. Methodology:The test procedure used non-parametric method of Data Envelopment Analysis. Data for analysis were draw from the Local Data Bank of the Central Statistical Office defining expenses in the transport section as well as data on the condition and use of transport infrastructure. The calculations have been made using Frontier Analyst Application software. The performance results were determined using the BCC model. Findings& Value added:The main result is the author's rankingof transport effectivenessin Polish cities. The analysis showed that urban transport characterized by a rather low technological effectiveness.
Keywords: O18; R58; C10; 330; technological effectiveness; urban transport; city management